Epizootological and epidemiological situation of anthrax in Ukraine in the context of mandatory specific prevention in susceptible animals - Korniienko, L. Y.; Ukhovskyi, V. V.; Moroz, O. A.; Chechet, O. M.; Haidei, O. S.; Tsarenko, T. M.; Bondarenko, T. M.; Karpulenko, M. S.; Nenych, N. P. (Regulatory Mechanisms in Biosystems, 2022)
The problem of zoonoses remains relevant in the context of reliable prevention of human disease and effective ways to achieve this result, in particular through the impact on susceptible animals by the efforts of veterinary medicine. Anthrax is an acute, particularly dangerous infectious disease of all species of farm, domestic and wild animals, as well as humans, which is caused by Bacillus anthracis microbes. The causative agent of anthrax belongs to the group of aerobic spore-forming bacteria and exists in two main forms: vegetative and spore. The vegetative form in the body of an infected animal can form a "capsule". In Ukraine, according to the provisions of the current "Instruction for the prevention and control of animal anthrax" (2000), the main method of preventing anthrax among animals is regular vaccination of animals susceptible to this disease. The authors conducted a retrospective analysis of the epizootic and epidemiological situation of anthrax in Ukraine for the period 1994–2021 and made a critical assessment of the performance of mandatory measures for specific prevention of susceptible animals. In order to find out the ecological and geographical features of the spread of anthrax, data on outbreaks of the disease in cattle, swine, small ruminants and humans on the territory of Ukraine were analyzed by regions for the time period under investigation. Over the past 28 years in Ukraine, animal anthrax was registered in in all areas except Zhytomyr region. In total, during the analyzed period, 177 affected points and 637 infected animals (cattle, small ruminants, pigs, horses, wild and fur-bearing animals, dogs) were registered (estimated at 3.59 animals per outbreak). Cattle were most often involved in the epizootic process, followed by pigs and small ruminants, while horses and other animal species were least infected. Ecological and geographical analysis showed that the largest number of affected points among animals during the analyzed period was found in Kyiv, Volyn, Kharkiv, Luhansk, Khmelnytskyi, Cherkasy, Odesa, and Vinnytsia regions. A small number of affected points during the analyzed period were found in Zakarpattia, Ternopil, Kherson, Autonomous Republic of Crimea, Poltava, Dnipropetrovsk and Ivano-Frankivsk regions. During the analyzed period, 68 people in 11 regions of Ukraine were infected with anthrax, 15 outbreaks were registered (4.46 people per outbreak). Most cases were reported in Donetsk, Kyiv and Odesa regions. The association between outbreaks of anthrax in animals and cases of anthrax among humans has been established, this dependency was 86.6% (the index of contiguity, which takes into account the number of years with simultaneous registration of animal and human cases, was 0.5). The authors thoroughly proved that it is vaccination among susceptible animals that will finally prevent the incidence of anthrax among people.